Porous zirconia-based composite oxide and method for producing porous zirconia-based composite oxide

By controlling the micropore distribution of zirconia-based composite oxides, the problem of macropore volume affecting specific surface area, heat resistance, and purification performance was solved, achieving stable catalyst performance at high temperatures.

CN119317603APending Publication Date: 2025-01-14DAIICHI KIGENSO KAGAKU KOGYO CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380044869.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-06
Filing Date
2023-05-30
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

When existing zirconia-based composite oxides are used as catalyst carriers for waste gas purification, the high mesopore volume leads to an increase in macropore volume, which affects the heat resistance of the specific surface area and the purification performance of the catalyst. Furthermore, the increase in macropores causes precious metals to be embedded inside the particles, affecting the purification effect.

Method used

By controlling the micropore distribution of zirconia-based composite oxides, the micropore volume in the range of 2nm to 200nm is kept within a specific range. This ensures that the maximum value of the dV/dlogD peak and the micropore volume meet specific conditions, thereby reducing the macropore volume and forming a structure with more mesopores and fewer macropores.

Benefits of technology

The heat resistance of the specific surface area of ​​zirconia-based composite oxides is improved, the phenomenon of precious metals being embedded in the particles during high-temperature heating is reduced, and the purification performance and operational stability of the catalyst are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119317603A_ABST
    Figure CN119317603A_ABST
Patent Text Reader

Abstract

A porous zirconia-based composite oxide which is characterized in that the following (1)-(3) are satisfied in the range of 2-200 nm inclusive in the pore distribution by the BJH method, the volume of pores in the range of more than 100 nm but not more than 1000 nm in the pore distribution by the mercury intrusion method is 0.01-0.25 cm < 3 > / g inclusive, (1) the dV / dlogD peak is in the range of 2-100 nm inclusive, (2) the maximum value of the dV / dlogD peak is 1.5-5.0 inclusive, and (3) the maximum value of the dV / dlogD peak is 0.5-5.0 inclusive. (3) The pore volume in the range of 2 nm to 100 nm (inclusive) is 0.30 cm < 3 > / g to 1.50 cm < 3 > / g (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a porous zirconia-based composite oxide and a method for producing the porous zirconia-based composite oxide. Background Art

[0002] The exhaust gas discharged from combustion engines such as automobiles or boilers contains harmful substances such as carbon monoxide (CO), hydrocarbons (HC), and nitrogen oxides (NOx), which can cause air pollution. From the perspective of preventing environmental pollution, it is an important issue to effectively purify these harmful substances, and research on exhaust gas purification catalysts that can simultaneously purify the above three components of harmful substances has been very active. In the above-mentioned exhaust gas purification catalyst, precious metals such as rhodium, palladium, and platinum are loaded on zirconium oxide composite oxides and then coated on honeycombs for use.

[0003] Patent document 1 discloses a zirconia-based porous body having peaks at pore sizes of 8 to 20 nm and 30 to 100 nm in a pore distribution based on the BJH method and a total pore volume of 0.4 cc / g or more, and a zirconia-based porous body having a peak at a pore size of 20 to 110 nm in a pore distribution based on the BJH method and a total pore volume of 0.4 cc / g or more (especially refer to claim 1).

[0004] Patent document 2 discloses a zirconia-based porous body, whose total pore volume after heat treatment at 1000°C for 3 hours is at least 0.75 ml / g, and the pore volume of pores with a diameter of 10 to 100 nm after heat treatment at 1000°C for 3 hours is at least 30% of the total pore volume (especially refer to claim 1).

[0005] Patent document 3 discloses a cerium-zirconium composite oxide, characterized in that the total pore volume is at least 0.4 ml / g, the pore volume with a diameter of 10 to 100 nm is greater than 0.25 ml / g, and the pore volume with a diameter of 100 nm to 10 μm is less than 0.2 ml / g (especially refer to claim 1).

[0006] Patent Document 4 discloses a zirconia-based porous body, (1) having a peak at a pore size of 20 to 100 nm in a pore distribution based on a BJH method, wherein the half-peak width of the peak obtained from a measured pore distribution curve is W, and the peak height is P, and the P / W ratio is 0.05 or more, and the total pore volume is 0.5 cm 3 / g or more, (2) after heat treatment at 1000°C for 12 hours, there is a peak at a pore size of 20 to 100 nm, and the P / W ratio is 0.03 cm 3 / g or more, with a specific surface area of ​​at least 40m 2 / g, with a total pore capacity of 0.3cm 3 / g (see in particular claim 1).

[0007] Patent document 5 discloses a mixed oxide of zirconium, cerium, lanthanum and optionally at least one rare earth metal (REM) other than cerium and lanthanum, wherein the weight ratio is: 8% to 45% of cerium, 1% to 10% of lanthanum, 0% to 15% of rare earth metal other than cerium and lanthanum, and the rest is zirconium, wherein the mixed oxide shows at least 30 m 2 The BET specific surface area of ​​​​the sample was 55 m / g after calcination at 1000 ° C for 4 hours. 2 The BET specific surface area of ​​1.377 W / g and the derivative curve (dV / dlogD) of the mixed oxide obtained by mercury intrusion porosimetry after calcination at 1100°C for 4 hours show that the maximum value of D is 24-34 nm in the range of pores with a diameter of less than 200 nm. p,1100℃ / 4h The peaks are equivalent to the pore diameters, V and D represent the pore volume and pore diameter, respectively (see claim 1 in particular). In addition, Patent Document 5 also discloses: the ratio defined by R = V1 / V2 (where V1 is the diameter in nm (D p,1100℃ / 4h -15)~(D p,1100℃ / 4h +15) is the pore volume of pores grown through pores with a diameter of less than 200 nm; V2 is the pore volume of pores grown through pores with a diameter of less than 200 nm, V1 and V2 are measured by mercury intrusion porosimetry of the mixed oxide after calcination at 1100°C for 4 hours) is greater than 0.60 (especially with reference to claim 7).

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2006-036576

[0011] Patent Document 2: Japanese Patent Application Publication No. 2008-081392

[0012] Patent Document 3: Japanese Patent Application Publication No. 2009-249275

[0013] Patent Document 4: Japanese Patent Application Publication No. 2015-189655

[0014] Patent Document 5: Japanese Patent Application No. 2019-521937 Summary of the invention

[0015] Problem that the invention aims to solve

[0016] The inventors of the present invention have conducted in-depth research on zirconium oxide composite oxides. As a result, it was found that in the past, in zirconium oxide composite oxides used as exhaust gas purification catalyst carriers, the volume of mesopores (diameter 2 to 50 nm) was increased in order to improve the heat resistance of the specific surface area. However, if the volume of the mesopores of the zirconium oxide composite oxide is increased, the volume of the macropores (50 nm or more) will also increase. In this specification, "heat resistance of specific surface area" means that the decrease in specific surface area due to heating is small.

[0017] Among the macropores, macropores having a diameter of 100 nm or more do not contribute to the improvement of the heat resistance of the specific surface area, and therefore have a problem in that they contribute little to the improvement of the function of the catalyst carrier.

[0018] Furthermore, the present inventors have found through careful studies that, in order to improve the heat resistance of the specific surface area, it is important to have a sharp peak in the mesopore region and to have a large pore volume in the mesopore region.

[0019] The present invention has been made in view of the above problems, and an object of the present invention is to provide a porous zirconia-based composite oxide having a small decrease in specific surface area due to heating, and also to provide a method for producing the porous zirconia-based composite oxide.

[0020] Solutions to the problem

[0021] The present invention provides the following solutions:

[0022] A porous zirconia-based composite oxide, characterized in that:

[0023] [1] In the range of 2 nm to 200 nm in pore size distribution based on the BJH method, the following (1) to (3) are satisfied,

[0024] The volume of pores in the range of more than 100 nm and less than or equal to 1000 nm in the pore distribution based on mercury intrusion porosimetry is 0.01 cm 3 / g above 0.25cm 3 / g or less,

[0025] (1) The dV / dlogD peak is within the range of 2nm to 100nm.

[0026] (2) the maximum value of the dV / dlogD peak is 1.5 or more and 5.0 or less,

[0027] (3) The pore volume in the range of 2 nm to 100 nm is 0.30 cm 3 / g above 1.50cm 3 / g or less.

[0028] According to the configuration of [1], since the dV / dlogD peak is within the range of 2 nm to 100 nm, the maximum value of the dV / dlogD peak is 1.5 or more, and the pore volume within the range of 2 nm to 100 nm is 0.30 cm 3 / g or more, it can be said that there is a sharp peak in the range of 2 nm to 100 nm, which contributes to the heat resistance of the specific surface area, and the pore volume is large.

[0029] In addition, the volume of pores in the range of more than 100 nm and less than or equal to 1000 nm is 0.25 cm 3 / g or less, it can be said that there are few pores that do not contribute to the heat resistance of the specific surface area.

[0030] In summary, according to the configuration of [1], it can be said that the decrease in specific surface area due to heating is small.

[0031] In addition, the large pores will cause the noble metals to be buried inside the particles due to the aggregation of the material at high temperature, making them ineffective for purification reactions, which is the main reason for the performance degradation. In addition, the increase in large pores leads to increased water absorption, which leads to poor operation during the preparation of the catalyst slurry.

[0032] On the other hand, according to the configuration of [1], since the pore volume in the range of 100 nm to 1000 nm is 0.25 cm 3 / g or less, so even if heated at high temperatures, the amount of precious metal buried inside the particles is small. Therefore, it is possible to suppress the performance degradation during high temperature heating. In addition, since the pore volume in the range of more than 100nm and less than or equal to 1000nm is 0.25cm 3 / g or less, so the water absorption is low and the operation during the catalyst slurry preparation is good.

[0033] From the viewpoint of measurement accuracy, for pores in the range of 2 nm to 100 nm, the value obtained by the BJH method is used, and for pores in the range of more than 100 nm to 1000 nm, the value obtained by the mercury porosimetry is used.

[0034] Specifically, for pores in the range of 2 nm to 100 nm, the value using the BJH method is used. This is because the BJH method is a pore measurement performed by gas adsorption, so the measurement accuracy of pores in the range of 2 nm to 200 nm is excellent, but for the range exceeding 200 nm, the gas adsorption method cannot be properly analyzed.

[0035] In addition, the value obtained by mercury porosimetry was used for pores in the range of more than 100 nm and less than or equal to 1000 nm because the gas adsorption method cannot appropriately measure the region of 200 nm or more.

[0036] It should be noted that Patent Documents 1 to 5 do not disclose that there is a sharp peak with a maximum value of dV / dlogD peak of 1.5 or more in the range of 2 nm to 100 nm, and that the pore volume of macropores of 100 nm or more is small. Therefore, in the zirconium oxide-based composite oxides such as Patent Documents 1 to 5, the effect of suppressing the decrease in specific surface area due to heating is poorer than that of the above-mentioned configuration [1].

[0037] In particular, in the graph of the derivative curve (dV / dlogD) obtained by mercury intrusion after heat treatment at 1100°C for 4 hours disclosed in Patent Document 5, the pore volume of macropores larger than 100 nm is relatively small. However, generally, macropores are easily reduced during heat treatment. That is, it cannot be said that the pore volume of macropores larger than 100 nm disclosed in Patent Document 5 is relatively small before heat treatment. The feature of the structure of [1] is that, before heat treatment, the pore volume of pores larger than 100 nm and smaller than or equal to 1000 nm is 0.25 cm 3 / g or less, Patent Document 5 does not disclose such a structure.

[0038] [2] In the configuration of [1],

[0039] The porous zirconia-based composite oxide satisfies the following (4) to (6) in a pore distribution of 2 nm to 200 nm based on the BJH method after heat treatment at 1000° C. for 3 hours in an air atmosphere at atmospheric pressure (0.1013 MPa),

[0040] The volume of pores in the range of more than 100 nm and less than or equal to 1000 nm in the pore distribution determined by mercury intrusion porosimetry after heat treatment at 1000°C for 3 hours under atmospheric pressure (0.1013 MPa) in air atmosphere was 0.01 cm 3 / g above 0.20cm 3 / g or less,

[0041] (4) The dV / dlogD peak is within the range of 2nm to 100nm.

[0042] (5) the maximum value of the dV / dlogD peak is 1.0 or more and 4.0 or less,

[0043] (6) The pore volume in the range of 2 nm to 100 nm is 0.25 cm 3 / g above 1.00cm 3 / g or less.

[0044] When the dV / dlogD peak after heat treatment at 1000°C for 3 hours is in the range of 2 nm to 100 nm, the maximum value of the dV / dlogD peak is 1.0 or more, and the pore volume in the range of 2 nm to 100 nm is 0.25 cm 3 When the surface area is 200 nm or more, even after heat treatment at 1000° C. for 3 hours, a sharp peak exists in the range of 2 nm to 100 nm which contributes to the heat resistance of the specific surface area, and it can be said that the pore volume is large.

[0045] In addition, the volume of pores in the range of more than 100 nm and less than or equal to 1000 nm after heat treatment at 1000°C for 3 hours was 0.20 cm 3 When the surface area is less than / g, it can be said that there are fewer pores which do not contribute to the heat resistance of the specific surface area.

[0046] In summary, according to the configuration of [2], it can be said that the decrease in specific surface area due to heating is smaller.

[0047] In addition, the same effect can be produced in an oxidizing atmosphere or a reducing atmosphere in which the catalyst is actually used.

[0048] [3] In the configuration of [1] or [2],

[0049] The specific surface area of ​​the porous zirconia composite oxide after heat treatment at 1000°C for 3 hours under atmospheric pressure and air atmosphere is 40 m 2 / g above 100m 2 / g or less.

[0050] When heat treated at 1000°C for 3 hours, the specific surface area is 40 m 2 When the specific surface area is 2.377 square meters or more by heating, it can be said that the decrease in specific surface area due to heating is smaller.

[0051] [4] In the configurations of [1] to [3],

[0052] The specific surface area (initial specific surface area) of porous zirconia composite oxide is 45 m 2 / g above 150m 2 / g or less.

[0053] When the specific surface area before heat treatment is 45m 2 When the specific surface area is greater than 100 μg, even if the specific surface area decreases to some extent due to heating, the specific surface area after heating can be maintained at a high level.

[0054] [5] The method for producing the porous zirconia-based composite oxide according to [1] to [4], comprising:

[0055] In the first step, a zirconium salt solution is heated at a temperature of 100° C. to 150° C. to generate a portion of hydrated zirconium oxide; and

[0056] The second step is to add a sulfating agent after the first step to obtain a slurry containing basic zirconium sulfate.

[0057] According to the structure of [5], first, the zirconium salt solution is heated at a temperature of not less than 100°C and not more than 150°C to generate hydrated zirconium oxide (first step), and then a sulfating agent is added (second step) to obtain particles having more mesopores and fewer macropores (slurry containing basic zirconium sulfate).

[0058] By generating basic zirconium sulfate using hydrated zirconium oxide as a core, particles having fewer macropores and more mesopores are formed.

[0059] As described above, according to the structure of [5], a porous zirconia-based composite oxide can be produced in which the pore diameter distribution in the mesopore region is clear, the volume of pores with a diameter of 10 nm to 100 nm is relatively large, and the volume of pores with a diameter of 100 nm to 1000 nm is relatively small.

[0060] Effects of the Invention

[0061] According to the present invention, a porous zirconia-based composite oxide having a small decrease in specific surface area due to heating can be provided, and a method for producing the porous zirconia-based composite oxide can also be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1 This is a graph showing the pore distribution of the porous zirconia-based composite oxide of Example 1 based on the BJH method.

[0063] Figure 2 This is a diagram showing the pore distribution of the porous zirconia-based composite oxide of Example 2 based on the BJH method.

[0064] Figure 3 This is a diagram showing the pore distribution of the porous zirconia-based composite oxide of Example 3 based on the BJH method.

[0065] Figure 4 This is a graph showing the pore distribution of the porous zirconia-based composite oxide of Example 4 based on the BJH method.

[0066] Figure 5 This is a graph showing the pore distribution of the porous zirconia-based composite oxide of Example 5 based on the BJH method.

[0067] Figure 6This is a graph showing the pore distribution of the porous zirconia-based composite oxide of Example 6 based on the BJH method.

[0068] Figure 7 This is a graph showing the pore distribution of the porous zirconia-based composite oxide of Comparative Example 1 based on the BJH method.

[0069] Figure 8 This is a diagram showing the pore distribution of the porous zirconia-based composite oxide of Comparative Example 2 based on the BJH method.

[0070] Fig. 9 This is a graph showing the pore distribution of the porous zirconia-based composite oxide of Comparative Example 3 based on the BJH method.

[0071] Fig.10 This is a graph showing the pore distribution of the porous zirconia-based composite oxide of Comparative Example 4 based on the BJH method.

[0072] Fig.11 This is a graph showing the pore distribution of the porous zirconia-based composite oxide of Example 1, as measured by mercury intrusion porosimetry.

[0073] Fig.12 This is a graph showing the pore distribution of the porous zirconia-based composite oxide of Example 2, as determined by mercury intrusion porosimetry.

[0074] Fig.13 This is a graph showing the pore distribution of the porous zirconia-based composite oxide of Example 3, as measured by mercury intrusion porosimetry.

[0075] Fig.14 This is a graph showing the pore distribution of the porous zirconia-based composite oxide of Example 4, as determined by mercury intrusion porosimetry.

[0076] Fig.15 This is a graph showing the pore distribution of the porous zirconia-based composite oxide of Example 5, as determined by mercury intrusion porosimetry.

[0077] Fig.16 This is a graph showing the pore distribution of the porous zirconia-based composite oxide of Example 6, as determined by mercury intrusion porosimetry.

[0078] Fig.17 This is a graph showing the pore distribution of the porous zirconia-based composite oxide of Comparative Example 1, as measured by mercury intrusion porosimetry.

[0079] Fig.18 This is a graph showing the pore distribution of the porous zirconia-based composite oxide of Comparative Example 2, as measured by mercury intrusion porosimetry.

[0080] Fig.19 Graph showing the pore distribution of the porous zirconia-based composite oxide of Comparative Example 3, as measured by mercury intrusion porosimetry.

[0081] Fig. 20 Graph showing the pore distribution of the porous zirconia-based composite oxide of Comparative Example 4 by mercury intrusion porosimetry. DETAILED DESCRIPTION

[0082] The embodiments of the present invention are described below. However, the present invention is not limited to these embodiments. In addition, in this specification, the porous zirconia-based composite oxide is a common porous zirconia-based composite oxide, which contains 10% by mass or less of an impurity metal compound containing hafnium. In addition, in this specification, expressions such as "containing" and "including" include the concepts of "containing", "including", "substantially consisting of", and "consisting only of".

[0083] The maximum value and the minimum value of the content of each component shown below are independent of the content of other components and are respectively the preferred minimum value and the preferred maximum value in the present invention.

[0084] In addition, the maximum values ​​and minimum values ​​of various parameters (measured values, etc.) shown below are independent of the content (composition) of each component and are respectively the preferred minimum value and maximum value of the present invention.

[0085] [Porous zirconia-based composite oxide]

[0086] The porous zirconia composite oxide of this embodiment will be described in detail later. It has zirconia as an essential component and is a composite oxide with oxides other than zirconia (other metal oxides). The use of the porous zirconia composite oxide of this embodiment is not particularly limited, and it can be used as an exhaust gas purification catalyst carrier. When used as an exhaust gas purification catalyst carrier, the catalyst that can be loaded can be a precious metal catalyst, etc.

[0087] <Pore volume before heat treatment>

[0088] The porous zirconia-based composite oxide of the present embodiment satisfies the following (1) to (3) within the range of 2 nm to 200 nm in pore size distribution based on the BJH method.

[0089] The volume of pores in the range of more than 100 nm and less than or equal to 1000 nm in the pore distribution based on mercury intrusion porosimetry is 0.01 cm 3 / g above 0.25cm 3 / g or less,

[0090] (1) The dV / dlogD peak is within the range of 2nm to 100nm.

[0091] (2) the maximum value of the dV / dlogD peak is 1.5 or more and 5.0 or less,

[0092] (3) The pore volume in the range of 2 nm to 100 nm is 0.30 cm 3 / g above 1.50cm 3 / g or less.

[0093] According to the porous zirconia-based composite oxide, the dV / dlogD peak is within the range of 2 nm to 100 nm, the maximum value of the dV / dlogD peak is 1.5 or more, and the pore volume within the range of 2 nm to 100 nm is 0.30 cm 3 / g or more, it can be said that there is a sharp peak in the range of 2 nm to 100 nm, which contributes to the heat resistance of the specific surface area, and the pore volume is large.

[0094] In addition, the volume of pores in the range of more than 100 nm and less than or equal to 1000 nm is 0.25 cm 3 / g or less, it can be said that there are few pores that do not contribute to the heat resistance of the specific surface area.

[0095] As described above, according to the porous zirconia-based composite oxide, it can be said that the decrease in specific surface area due to heating is small.

[0096] In addition, the large pores will cause the noble metals to be buried inside the particles due to the aggregation of the material at high temperature, making them ineffective for purification reactions, which is the main reason for the performance degradation. In addition, the increase in large pores leads to increased water absorption, which leads to poor operation during the preparation of the catalyst slurry.

[0097] On the other hand, according to the porous zirconia-based composite oxide, the pore volume in the range of 100 nm to 1000 nm is 0.25 cm 3 / g or less, so even if heated at high temperatures, the amount of precious metal buried inside the particles is small. Therefore, it is possible to suppress the performance degradation during high temperature heating. In addition, since the pore volume in the range of more than 100nm and less than or equal to 1000nm is 0.25cm 3 / g or less, so the water absorption is low and the operation during the catalyst slurry preparation is good.

[0098] The dV / dlogD peak in (1) is preferably within a range of 5 nm to 95 nm, and more preferably within a range of 10 nm to 80 nm.

[0099] The maximum value of the dV / dlogD peak in (2) is preferably 1.7 or more, more preferably 2.0 or more. The maximum value of the dV / dlogD peak is preferably as large as possible, for example, 4.0 or less, 4.5 or less.

[0100] The pore volume in the range of 2 nm to 100 nm in (3) is preferably 0.35 cm 3 / g or more, more preferably 0.40cm 3 The pore volume in the range of 2 nm to 100 nm is as large as possible, for example, 1.30 cm 3 / g or less, 1.40cm 3 / g or below.

[0101] The volume of pores in the range of greater than 100 nm and less than or equal to 1000 nm is preferably 0.22 cm 3 / g or less, more preferably 0.20cm 3 The pore volume in the range of more than 100 nm and less than or equal to 1000 nm is as small as possible, for example, 0.02 cm 3 / g or more, 0.05cm 3 / g and above.

[0102] As a method of satisfying the above (1) to (3), the volume of pores in the range of more than 100 nm and less than or equal to 1000 nm is adjusted to 0.01 cm 3 / g above 0.25cm 3 The method for adjusting the content of Mg to Mg / g or less is not particularly limited, and for example, the method may be a method of adjusting the content of Mg to Mg by the production method described below.

[0103] The porous zirconia-based composite oxide preferably has a pore volume of 0.50 cm-1 in the total measurement range (0.0036 μm to 10.3 μm) of the pore distribution by mercury intrusion porosimetry. 3 / g above 2.50cm 3 When the pore volume of the total measurement range (0.0036 μm to 10.3 μm) in the pore distribution based on the mercury intrusion method is 0.70 cm 3 When the content of MgO2 / g is greater than that of CuO2 / g, the performance as a catalyst carrier is more excellent.

[0104] The pore volume of the total measurement range (0.0036 μm to 10.3 μm) is preferably 0.70 cm 3 / g or more, more preferably 1.00cm 3 The larger the pore volume in the total measurement range (0.0036 μm to 10.3 μm), the better. For example, 2.00 cm 3 / g or less, 2.30cm 3 / g or below.

[0105] <Pore volume after heat treatment at 1000°C for 3 hours>

[0106] The porous zirconia-based composite oxide satisfies the following (4) to (6) in a pore distribution of 2 nm to 200 nm based on a BJH method after heat treatment at 1000° C. for 3 hours under atmospheric pressure and air atmosphere,

[0107] The volume of pores in the range of more than 100 nm and less than or equal to 1000 nm in the pore distribution determined by mercury intrusion porosimetry after heat treatment at 1000°C for 3 hours under atmospheric pressure and air atmosphere is preferably 0.01 cm 3 / g above 0.20cm 3 / g or less,

[0108] (4) The dV / dlogD peak is within the range of 2nm to 100nm.

[0109] (5) The maximum value of the dV / dlogD peak is 1.0 or more and 4.0 or less,

[0110] (6) The pore volume in the range of 2 nm to 100 nm is 0.25 cm 3 / g above 1.00cm 3 / g or less.

[0111] When the dV / dlogD peak after heat treatment at 1000°C for 3 hours is in the range of 2 nm to 100 nm, the maximum value of the dV / dlogD peak is 1.0 or more, and the pore volume in the range of 2 nm to 100 nm is 0.25 cm 3 When the surface area is 200 nm or more, even after heat treatment at 1000° C. for 3 hours, a sharp peak exists in the range of 2 nm to 100 nm which contributes to the heat resistance of the specific surface area, and it can be said that the pore volume is large.

[0112] In addition, the volume of pores in the range of more than 100 nm and less than or equal to 1000 nm after heat treatment at 1000°C for 3 hours was 0.20 cm 3 When the surface area is less than / g, it can be said that there are fewer pores which do not contribute to the heat resistance of the specific surface area.

[0113] In summary, if the above (4) to (6) are satisfied and the volume of pores in the range of more than 100 nm and less than or equal to 1000 nm after heat treatment at 1000°C for 3 hours is 0.20 cm 3 / g or less, it can be said that the decrease in specific surface area due to heating is smaller.

[0114] The dV / dlogD peak after heat treatment at 1000° C. for 3 hours in (4) is preferably in the range of 5 nm to 95 nm, more preferably in the range of 10 nm to 90 nm.

[0115] The maximum value of the dV / dlogD peak after heat treatment at 1000°C for 3 hours in (5) is preferably 1.2 or more, more preferably 1.4 or more. The maximum value of the dV / dlogD peak is preferably as large as possible, for example, 3.3 or less, 3.5 or less.

[0116] The pore volume in the range of 2 nm to 100 nm in (6) after heat treatment at 1000°C for 3 hours is preferably 0.27 cm 3 / g or more, more preferably 0.30cm 3 The pore volume in the range of 2 nm to 100 nm is as large as possible, for example, 0.90 cm 3 / g or less, 0.95cm 3 / g or below.

[0117] The volume of the pores in the range of greater than 100 nm and less than or equal to 1000 nm after heat treatment at 1000° C. for 3 hours is preferably 0.19 cm 3 / g or less, more preferably 0.18cm 3 The pore volume in the range of more than 100 nm and less than or equal to 1000 nm is as small as possible, for example, 0.02 cm 3 / g or more, 0.05cm 3 / g and above.

[0118] The above conditions (4) to (6) are satisfied, and the volume of pores in the range of more than 100 nm and less than or equal to 1000 nm after heat treatment at 1000°C for 3 hours is adjusted to 0.01 cm 3 / g above 0.20cm 3 The method for adjusting the content of Mg to Mg / g or less is not particularly limited, and for example, the method may be a method of adjusting the content of Mg to Mg by the production method described below.

[0119] The porous zirconia-based composite oxide preferably has a pore volume of 0.50 cm-1 in the total measurement range (0.0036 μm to 10.3 μm) in the pore distribution by mercury intrusion after heat treatment at 1000° C. for 3 hours. 3 / g above 2.00cm 3 The pore volume of the total measurement range (0.0036 μm to 10.3 μm) in the pore distribution by mercury intrusion porosimetry after heat treatment at 1000°C for 3 hours was 0.50 cm 3 When the content of MgO2 / g is greater than that of CuO2 / g, the performance as a catalyst carrier is more excellent.

[0120] The pore volume of the total measurement range (0.0036 μm to 10.3 μm) after heat treatment at 1000°C for 3 hours is preferably 0.60 cm 3 / g or more, more preferably 0.70cm 3 The pore volume of the total measurement range (0.0036 μm or more and 10.3 μm or less) after heat treatment at 1000°C for 3 hours is preferably as large as possible, for example, 1.80 cm 3 / g or less, 1.90cm 3 / g or below.

[0121] The details of the method for measuring the pore distribution by the BJH method and the pore distribution by the mercury intrusion method are the same as the method described in the Examples.

[0122] <Specific surface area after heat treatment at 1000°C for 3 hours under atmospheric pressure and air atmosphere>

[0123] The specific surface area of ​​the porous zirconia-based composite oxide after heat treatment at 1000° C. for 3 hours under atmospheric pressure and air atmosphere is preferably 45 m 2 / g above 100m 2 / g or less. When heat treated at 1000°C for 3 hours under atmospheric pressure and air atmosphere, the specific surface area is 45m 2 When the specific surface area is 2.377 square meters or more by heating, it can be said that the decrease in specific surface area due to heating is smaller.

[0124] The specific surface area after heat treatment at 1000°C for 3 hours is preferably 48 m 2 / g or more, more preferably 50m 2 / g or more, more preferably 55m 2 / g or above.

[0125] The specific surface area after heat treatment at 1000°C for 3 hours is as large as possible, for example, 90 m 2 / g or less, 95m 2 / g or below.

[0126] It should be noted that the specific surface area after heat treatment at 1000° C. for 3 hours generally does not increase compared to the specific surface area before the heat treatment, and if the heat resistance is high, it remains at the same level as or slightly lower than that before the heat treatment.

[0127] <Specific surface area after heat treatment at 1100°C for 3 hours under atmospheric pressure and air atmosphere>

[0128] The specific surface area of ​​the porous zirconia composite oxide after heat treatment at 1100° C. for 3 hours under atmospheric pressure and air atmosphere is preferably 15 m 2 / g above 70m2 / g or less. When heat treated at 1100°C for 3 hours under atmospheric pressure and air atmosphere, the specific surface area is 15m 2 When the specific surface area is 2.377 square meters or more by heating, it can be said that the decrease in specific surface area due to heating is smaller.

[0129] It should be noted that the specific surface area after heat treatment at 1100° C. for 3 hours is generally lower than the specific surface area before heat treatment and the specific surface area after heat treatment at 1000° C. for 3 hours.

[0130] The specific surface area after heat treatment at 1100°C for 3 hours is preferably 18 m 2 / g or more, more preferably 20m 2 / g or more, more preferably 22m 2 / g or above.

[0131] The specific surface area after heat treatment at 1100°C for 3 hours is as large as possible, for example, 60 m 2 / g or less, 65m 2 / g or below.

[0132] <Specific surface area (initial specific surface area)>

[0133] The specific surface area (initial specific surface area) of the porous zirconia-based composite oxide is preferably 45 m 2 / g above 150m 2 / g or less. When the specific surface area is 45m 2 When the specific surface area is greater than 100 g, even if the specific surface area is somewhat reduced due to heating, the specific surface area after heating can be maintained at a high level. Here, the specific surface area (initial specific surface area) refers to the specific surface area of ​​the porous zirconia composite oxide after it is manufactured without being subjected to heating treatment or pulverization treatment.

[0134] The specific surface area is preferably 47 m 2 / g or more, more preferably 50m 2 / g or more, more preferably 52m 2 / g or above.

[0135] The larger the specific surface area, the better, for example, 140m 2 / g or less, 145m 2 / g or below.

[0136] The specific surface area after heat treatment at 1000° C. for 3 hours, the specific surface area after heat treatment at 1100° C. for 3 hours, and the specific surface area (initial specific surface area) are values ​​obtained by the method described in Examples.

[0137] <Particle size>

[0138] The particle size D of the porous zirconia-based composite oxide is 50 It is preferably 1.0 μm or more and 30.0 μm or less. 50 It is more preferably 1.5 μm or more, and even more preferably 2.0 μm or more. 50 The diameter is more preferably 29.0 μm or less, and further preferably 28.0 μm or less.

[0139] When the particle size D 50 When the particle size is 1.0 μm or more and 30.0 μm or less, the catalyst can be suitably used as a catalyst carrier.

[0140] The particle size D of the porous zirconia-based composite oxide is 10 It is preferably 0.5 μm or more and 10.0 μm or less. 10 It is more preferably 0.6 μm or more, and even more preferably 0.7 μm or more. 10 The diameter is more preferably 9.5 μm or less, and even more preferably 9.0 μm or less.

[0141] When the particle size D 10 When the particle size is 0.5 μm or more and 10.0 μm or less, the catalyst can be suitably used as a catalyst carrier.

[0142] The particle size D of the porous zirconia-based composite oxide is 90 It is preferably 5.0 μm or more and 100.0 μm or less. 90 It is more preferably 7.0 μm or more, and even more preferably 10.0 μm or more. 90 The diameter is more preferably 90.0 μm or less, and still more preferably 80.0 μm or less.

[0143] When the particle size D 90 When the particle size is 5.0 μm or more and 100.0 μm or less, the catalyst can be suitably used as a catalyst carrier.

[0144] The particle size D 10 , the particle size D 50 , the particle size D 90 It refers to the particle size of the porous zirconia-based composite oxide after it is produced but not subjected to pulverization or heat treatment. The above-mentioned "pulverization" means fine pulverization, which means pulverization by a common method such as a planetary mill, a ball mill, or a jet mill.

[0145] The particle size D 10 , the particle size D 50 , the particle size D 90 These are values ​​obtained by the methods described in the Examples.

[0146] <Composition>

[0147] The porous zirconia composite oxide contains zirconia. When the porous zirconia composite oxide is 100% by mass as a whole, the content of the zirconia is preferably 30% by mass or more, more preferably 35% by mass or more, further preferably 40% by mass or more, and particularly preferably 45% by mass or more. There is no particular restriction on the upper limit of the content of the zirconia, and the content of the zirconia is preferably 95% by mass or less, more preferably 92% by mass or less, further preferably 90% by mass or less, and particularly preferably 85% by mass or less. When the content of the zirconia is 30% by mass or more and 95% by mass or less, it can be suitably used as a catalyst carrier.

[0148] The porous zirconia-based composite oxide preferably contains oxides of one or more elements selected from rare earth elements.

[0149] The rare earth elements include Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu. However, the porous zirconia composite oxide preferably does not contain Pm. That is, the porous zirconia composite oxide more preferably contains an oxide of one or more elements selected from the rare earth elements other than Pm.

[0150] When the oxide of one or more elements selected from rare earth elements other than Pm is contained, the thermal stability of the specific surface area can be improved, that is, the change in the specific surface area before and after exposure to high temperature can be reduced, so that the catalytic performance will not be greatly reduced.

[0151] Among the rare earth elements, Y (yttrium), La (lanthanum), Ce (cerium), Nd (neodymium), and Pr (praseodymium) are preferred. That is, the porous zirconia-based composite oxide preferably contains an oxide of one or more elements selected from the group consisting of lanthanum oxide, cerium oxide, neodymium oxide, praseodymium oxide, and yttrium oxide.

[0152] The porous zirconia-based composite oxide may further contain oxides of one or more elements selected from the group consisting of:

[0153] A) oxides of one or more elements selected from the group consisting of Al, In, Si, Sn, Bi, P and Zn,

[0154] B) transition metal oxides (except oxides of rare earth elements and precious metal elements),

[0155] C) alkaline earth metal oxides,

[0156] D) Platinum group metals.

[0157] Hereinafter, in this specification, the elements indicated by A) to D) are referred to as "other elements". When the porous zirconia-based composite oxide contains oxides of the other elements, when the porous zirconia-based composite oxide as a whole is 100% by mass, the content of the oxides of the other elements may be 0.1% by mass or more in terms of oxide conversion. The upper limit of the content of the oxides of the other elements is not particularly limited, and may be 20% by mass or less, 10% by mass or less, 7% by mass or less, 5% by mass or less, etc.

[0158] The transition metal may be, for example, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Nb, Mo, Ta, W, Ag, etc. The alkaline earth metal may be Mg, Ca, Sr, Ba, etc. The platinum group metal may be Rh, Pd, Pt, Ir, etc.

[0159] In the porous zirconia-based composite oxide, the total content of zirconia and rare earth oxides is preferably 80% by mass or more and 100% by mass or less. The total content of zirconia and rare earth oxides is more preferably 85% by mass or more, and further preferably 90% by mass or more. The total content of zirconia and rare earth oxides is more preferably 99% by mass or less, and further preferably 98% by mass or less.

[0160] The preferred composition ratio of the porous zirconia-based composite oxide may be a combination of the following (1) to (4) as examples, the total of which does not exceed 100%:

[0161] (1) Zirconium oxide: 40 mass % to 95 mass %,

[0162] Rare earth oxides: 5 mass % to 60 mass %,

[0163] Oxides of other elements: 0 mass % or more and 20 mass % or less,

[0164] (2) Zirconium oxide: 43% by mass or more and 90% by mass or less,

[0165] Rare earth oxides: 10 mass % to 55 mass %.

[0166] Oxides of other elements: 1 mass % to 15 mass %,

[0167] (3) Zirconium oxide: 45 mass % to 75 mass %,

[0168] Rare earth oxides: 15% to 50% by mass,

[0169] Oxides of other elements: 1 mass % to 10 mass %,

[0170] (4) Zirconium oxide: 50 mass % to 70 mass %,

[0171] Rare earth oxides: 16 mass % to 45 mass %,

[0172] Oxides of other elements: 1 mass % to 5 mass %.

[0173] The composition of the porous zirconia-based composite oxide is determined by the method described in Examples.

[0174] [Method for producing porous zirconia-based composite oxide]

[0175] An example of a method for producing a porous zirconia-based composite oxide is described below. However, the method for producing a porous zirconia-based composite oxide of the present invention is not limited to the following example.

[0176] The method for producing the porous zirconia-based composite oxide of the present embodiment includes:

[0177] In the first step, a zirconium salt solution is heated at a temperature of 100° C. to 150° C. to generate a portion of hydrated zirconium oxide; and

[0178] The second step is to add a sulfating agent after the first step to obtain a slurry containing basic zirconium sulfate.

[0179] In the method for producing a porous zirconium oxide composite oxide of the present embodiment, first, a zirconium salt solution is heated and hydrolyzed at a temperature of 100° C. to 150° C. to generate hydrated zirconium oxide (first step). Then (after the first step), a sulfating agent is added to obtain a slurry containing basic zirconium sulfate (second step).

[0180] By heating the zirconium salt solution at 100°C to 150°C to hydrolyze it to generate hydrated zirconium oxide, and then adding a sulfating agent, particles with few mesopores and few macropores (slurry containing basic zirconium sulfate) can be obtained.

[0181] The heating temperature in the above step is preferably 105° C. or higher, and more preferably 110° C. or higher. The heating temperature in the above step is preferably 145° C. or lower, and more preferably 140° C. or lower.

[0182] The heating time is preferably not less than 20 minutes and not more than 10 hours. The heating time is more preferably not less than 30 minutes, and further preferably not less than 40 minutes. The heating time is more preferably not more than 9 hours, and further preferably not more than 8 hours. By making the mixing time within the time range, the generated basic zirconium sulfate can be properly matured. Basic zirconium sulfate is not particularly limited, and for example, it can be a hydrate of compounds such as ZrOSO4·ZrO2, 5ZrO2·3SO3, and 7ZrO2·3SO3. It should be noted that the basic zirconium sulfate can be one or a mixture of two or more thereof.

[0183] The heating and mixing can be performed under atmospheric pressure or under pressure. When performed under pressure, the pressure is not particularly limited, and the absolute pressure is preferably 0.10 MPa or more, and more preferably 0.11 MPa or more. In addition, the pressure is not particularly limited, but is preferably 0.8 MPa or less, 0.6 MPa or less, or 0.55 MPa.

[0184] After the mixing, the reaction solution is preferably cooled to 60° C. or less.

[0185] The cooling is preferably below 50°C, more preferably below 40°C. The lower limit temperature of the cooling is not particularly limited, but it is preferably a temperature at which the reaction solution does not freeze, for example, it can be above 10°C, above 20°C, etc. The cooling rate does not need to be particularly controlled, and can be naturally cooled. However, in the case of a large scale, since natural cooling takes time, a heat exchanger or the like can also be used for cooling. At this time, the cooling rate can be appropriately set within the range of, for example, 0.1°C / min to 20°C / min.

[0186] The sulfating agent is not particularly limited, for example, it can be sodium sulfate, potassium sulfate, ammonium sulfate, etc., as long as it is a substance that reacts with zirconium ions to generate sulfate (i.e., a reagent for sulfation). The sulfating agent can be in any form such as powder or solution, but a solution (particularly an aqueous solution) is preferred. The solution concentration when using a solution can be appropriately set.

[0187] The free acid concentration of the mixed solution is preferably 0.2 to 2.2 N (specified). The free acid may be sulfuric acid, nitric acid, hydrochloric acid, etc. The type of the free acid is not particularly limited, but hydrochloric acid is preferred from the viewpoint of high productivity on an industrial scale.

[0188] For example, zirconium oxynitrate, zirconium oxychloride, zirconium nitrate, etc. can be used as the zirconium salt, and any zirconium salt that supplies zirconium ions may be used. One or more of these may be used.

[0189] The solvent used to prepare the zirconium salt solution may be selected according to the type of zirconium salt, and water (pure water, ion-exchanged water) is usually preferred.

[0190] The concentration of the zirconium salt solution is not particularly limited, but it is usually preferred that 5 to 250 g (particularly 20 to 150 g) of zirconium oxide (ZrO 2 ) is contained in 1000 g of the solvent.

[0191] It should be noted that the size of the mesopores and the pore volume can be adjusted to be within a preferred range by adjusting the amount of the sulfating agent added.

[0192] The more sulfation agent is added, the larger the size of the mesopores tends to be, and the larger the volume of the pores tends to be.

[0193] The sulfating agent added is preferably in the form of sulfate (SO4 2- ) / ZrO2 is added in a weight ratio of 0.3 to 0.7.

[0194] Thereafter, when the porous zirconia-based composite oxide contains oxides of one or more elements selected from the group consisting of rare earth elements and other elements, a specified amount of a salt solution or compound of one or more metals selected from the group consisting of rare earth elements and other elements is added to a slurry containing basic zirconium sulfate before the neutralization step described later.

[0195] The above process is preferably carried out in an autoclave in which temperature and pressure can be easily controlled.

[0196] Next, zirconium hydroxide is generated by neutralizing the basic zirconium sulfate. Specifically, zirconium hydroxide is produced by neutralizing the basic zirconium sulfate with an alkali. The alkali is not particularly limited, and for example, ammonium hydroxide, ammonium bicarbonate, sodium hydroxide, potassium hydroxide, etc. can be used. Among them, sodium hydroxide is preferred from the perspective of industrial cost.

[0197] The amount of the base added is not particularly limited as long as zirconium hydroxide can be generated as a precipitate from the basic zirconium sulfate solution. The base is usually added so that the pH of the solution is 11 or higher, preferably 12 or higher.

[0198] After the neutralization reaction, the zirconium hydroxide-containing solution is preferably kept at 35 to 60° C. for 1 hour or more. This allows the generated precipitate to mature and facilitates separation by filtration.

[0199] Next, zirconium hydroxide is recovered by solid-liquid separation, for example, by filtration, centrifugal separation, decantation, etc.

[0200] After the zirconium hydroxide is recovered, it is preferably washed with water to remove adhering impurities.

[0201] Zirconium hydroxide can be dried by natural drying or heat drying.

[0202] Next, the zirconium hydroxide is heat treated (calcined) to obtain a porous zirconium oxide composite oxide. The heat treatment temperature is not particularly limited, but is preferably about 400 to 900° C. for about 1 to 5 hours. The heat treatment atmosphere is preferably air or an oxidizing atmosphere.

[0203] The obtained porous zirconia-based composite oxide may be subjected to a decomposition and aggregation treatment for the purpose of improving handleability or the like, as necessary.

[0204] The method for producing the porous zirconia-based composite oxide according to the present embodiment has been described above.

[0205] [Example]

[0206] The present invention is described in detail below with reference to the examples, but the present invention is not limited to the following examples unless the gist of the present invention is exceeded. It should be noted that the porous zirconia-based composite oxides obtained in the examples and comparative examples contain 1 to 3% by mass of hafnium as an inevitable impurity relative to zirconium (calculated by the following formula (X)).

[0207] <Formula (X)>

[0208] ([Mass of hafnium] / ([Mass of zirconium]+[Mass of hafnium])×100(%)

[0209] The maximum and minimum values ​​of the content of each component shown in the following examples are independent of the contents of other components and should be regarded as the preferred minimum and maximum values ​​of the present invention.

[0210] The maximum and minimum values ​​of the measured values ​​shown in the following examples have nothing to do with the content (composition) of each component, and should be regarded as the preferred minimum and maximum values ​​of the present invention.

[0211] [Preparation of Porous Zirconia-Based Composite Oxide]

[0212] (Example 1)

[0213] 117 g of zirconium oxynitrate dihydrate (54 g in terms of ZrO 2 ) was dissolved in ion exchange water, and the ZrO 2 concentration was adjusted to 10 wt / v % (mass volume % concentration) to obtain a zirconium salt solution.

[0214] The obtained solution was placed in an autoclave, heated to 120°C and maintained for 1 hour, then 756 g of 5% sodium sulfate (sulfating agent) was added and maintained for 30 minutes. Then, the solution was cooled to room temperature (25°C) to obtain a slurry containing basic zirconium sulfate.

[0215] To the slurry containing basic zirconium sulfate, 300 g of cerium nitrate solution (converted to CeO2: 30 g), 80 g of neodymium nitrate solution (converted to Nd2O3: 8 g), and 80 g of praseodymium nitrate solution (converted to Pr6O 11 :8g).

[0216] Next, 500 g of 25% sodium hydroxide (alkali for neutralization) was added over 60 minutes to generate a hydroxide precipitate (slurry containing zirconium hydroxide).

[0217] The obtained hydroxide precipitate was filtered and washed thoroughly with water, and the obtained hydroxide was dried at 105° C. for 24 hours. The dried hydroxide was heat treated (calcined) at 700° C. for 5 hours in air to obtain the porous zirconia-based composite oxide of Example 1.

[0218] (Example 2)

[0219] 119 g of zirconium oxynitrate dihydrate (55 g in terms of ZrO 2 ) was dissolved in ion exchange water, and the ZrO 2 concentration was adjusted to 10 wt / v % to obtain a zirconium salt solution.

[0220] The obtained solution was placed in an autoclave, heated to 110°C and maintained for 1 hour, then 770 g of 5% sodium sulfate (sulfating agent) was added and maintained for 30 minutes. Then, the solution was cooled to room temperature (25°C) to obtain a slurry containing basic zirconium sulfate.

[0221] To the slurry containing basic zirconium sulfate were added 400 g of cerium nitrate solution (40 g in terms of CeO 2 ) and 50 g of lanthanum nitrate solution (5 g in terms of La 2 O 3 ).

[0222] Next, 500 g of 25% sodium hydroxide (alkali for neutralization) was added over 60 minutes to generate a hydroxide precipitate (slurry containing zirconium hydroxide).

[0223] The obtained hydroxide precipitate was filtered and washed thoroughly with water, and the obtained hydroxide was dried at 105° C. for 24 hours. The dried hydroxide was heat treated (calcined) at 800° C. for 5 hours in air to obtain the porous zirconia-based composite oxide of Example 2.

[0224] (Example 3)

[0225] 98 g of zirconium oxynitrate dihydrate (45 g in terms of ZrO 2 ) was dissolved in ion exchange water, and the ZrO 2 concentration was adjusted to 10 wt / v % to obtain a zirconium salt solution.

[0226] The obtained solution was placed in an autoclave, heated to 120°C and maintained for 1 hour, then 630 g of 5% sodium sulfate (sulfating agent) was added and maintained for 30 minutes. Then, the solution was cooled to room temperature (25°C) to obtain a slurry containing basic zirconium sulfate.

[0227] To the slurry containing basic zirconium sulfate were added 500 g of a cerium nitrate solution (50 g in terms of CeO 2 ) and 50 g of a lanthanum nitrate solution (5 g in terms of La 2 O 3 ).

[0228] Next, 500 g of 25% sodium hydroxide (alkali for neutralization) was added over 60 minutes to generate a hydroxide precipitate (slurry containing zirconium hydroxide).

[0229] The obtained hydroxide precipitate was filtered and washed thoroughly with water, and the obtained hydroxide was dried at 105° C. for 24 hours. The dried hydroxide was heat treated (calcined) at 650° C. for 5 hours in air to obtain the porous zirconia-based composite oxide of Example 3.

[0230] (Example 4)

[0231] 152 g of zirconium oxynitrate dihydrate (70 g in terms of ZrO 2 ) was dissolved in ion exchange water, and the ZrO 2 concentration was adjusted to 10 wt / v % to obtain a zirconium salt solution.

[0232] The obtained solution was placed in an autoclave, heated to 120°C and maintained for 1 hour, then 1250 g of 5% sodium sulfate (sulfating agent) was added and maintained for 60 minutes. Then, the solution was cooled to room temperature (25°C) to obtain a slurry containing basic zirconium sulfate.

[0233] To the slurry containing basic zirconium sulfate were added 200 g of cerium nitrate solution (converted to CeO2: 20 g), 20 g of lanthanum nitrate solution (converted to La2O3: 2 g), and 80 g of neodymium nitrate solution (converted to Nd2O3: 8 g).

[0234] Next, 500 g of 25% sodium hydroxide (alkali for neutralization) was added over 60 minutes to generate a hydroxide precipitate (slurry containing zirconium hydroxide).

[0235] The obtained hydroxide precipitate was filtered and washed thoroughly with water, and the obtained hydroxide was dried at 105° C. for 24 hours. The dried hydroxide was heat treated (calcined) at 700° C. for 5 hours in air to obtain the porous zirconia-based composite oxide of Example 4.

[0236] (Example 5)

[0237] 130 g of zirconium oxynitrate dihydrate (70 g in terms of ZrO 2 ) was dissolved in ion exchange water, and the ZrO 2 concentration was adjusted to 10 wt / v % to obtain a zirconium salt solution.

[0238] The obtained solution was placed in an autoclave, heated to 120°C and maintained for 1 hour, then 977 g of 5% sodium sulfate (sulfating agent) was added and maintained for 30 minutes. Then, the solution was cooled to room temperature (25°C) to obtain a slurry containing basic zirconium sulfate.

[0239] To the slurry containing basic zirconium sulfate were added 200 g of cerium nitrate solution (converted to CeO2: 20 g), 20 g of lanthanum nitrate solution (converted to La2O3: 2 g), and 80 g of neodymium nitrate solution (converted to Nd2O3: 8 g).

[0240] Next, 500 g of 25% sodium hydroxide (alkali for neutralization) was added over 60 minutes to generate a hydroxide precipitate (slurry containing zirconium hydroxide).

[0241] The obtained hydroxide precipitate was filtered and washed thoroughly with water, and the obtained hydroxide was dried at 105° C. for 24 hours. The dried hydroxide was heat treated (calcined) at 700° C. for 5 hours in air to obtain a porous zirconia-based composite oxide of Example 5.

[0242] (Example 6)

[0243] 98 g of zirconium oxynitrate dihydrate (60 g in terms of ZrO 2 ) was dissolved in ion exchange water, and the ZrO 2 concentration was adjusted to 10 wt / v % to obtain a zirconium salt solution.

[0244] The obtained solution was placed in an autoclave, heated to 120°C and maintained for 1 hour, then 866 g of 5% sodium sulfate (sulfating agent) was added and maintained for 30 minutes. Then, the solution was cooled to room temperature (25°C) to obtain a slurry containing basic zirconium sulfate.

[0245] To the slurry containing basic zirconium sulfate were added 300 g of cerium nitrate solution (converted to CeO2: 30 g), 30 g of lanthanum nitrate solution (converted to La2O3: 3 g), and 70 g of neodymium nitrate solution (converted to Nd2O3: 7 g).

[0246] Next, 500 g of 25% sodium hydroxide (alkali for neutralization) was added over 60 minutes to generate a hydroxide precipitate (slurry containing zirconium hydroxide).

[0247] The obtained hydroxide precipitate was filtered and washed thoroughly with water, and the obtained hydroxide was dried at 105° C. for 24 hours. The dried hydroxide was heat treated (calcined) at 700° C. for 5 hours in air to obtain a porous zirconia-based composite oxide of Example 6.

[0248] (Example 7)

[0249] 108 g of zirconium oxynitrate dihydrate (converted to ZrO 2 : 50 g) was dissolved in ion exchange water, and the ZrO 2 concentration was adjusted to 8 wt / v % to obtain a zirconium salt solution.

[0250] The obtained solution was placed in an autoclave, heated to 120°C and maintained for 1 hour, then 700 g of 5% sodium sulfate (sulfating agent) was added and maintained for 15 minutes. Then, the solution was cooled to room temperature (25°C) to obtain a slurry containing basic zirconium sulfate.

[0251] To the slurry containing basic zirconium sulfate were added 350 g of cerium nitrate solution (converted to CeO2: 35 g), 30 g of lanthanum nitrate solution (converted to La2O3: 3 g), and 120 g of neodymium nitrate solution (converted to Y2O3: 12 g).

[0252] Next, 500 g of 25% sodium hydroxide (alkali for neutralization) was added over 60 minutes to generate a hydroxide precipitate (slurry containing zirconium hydroxide).

[0253] The obtained hydroxide precipitate was filtered and washed thoroughly with water, and the obtained hydroxide was dried at 105° C. for 24 hours. The dried hydroxide was heat treated (calcined) at 700° C. for 5 hours in air to obtain a porous zirconia-based composite oxide of Example 7.

[0254] (Example 8)

[0255] 137 g of zirconium oxynitrate dihydrate (63 g in terms of ZrO 2 ) was dissolved in ion exchange water, and the ZrO 2 concentration was adjusted to 11 wt / v % to obtain a zirconium salt solution.

[0256] The obtained solution was placed in an autoclave, heated to 120°C and maintained for 1 hour, then 882 g of 5% sodium sulfate (sulfating agent) was added and maintained for 15 minutes, and then cooled to room temperature (25°C) to obtain a slurry containing basic zirconium sulfate.

[0257] To the slurry containing basic zirconium sulfate were added 120 g of a lanthanum nitrate solution (12 g in terms of La2O3) and 250 g of a yttrium nitrate solution (25 g in terms of Y2O3).

[0258] Next, 500 g of 25% sodium hydroxide (alkali for neutralization) was added over 60 minutes to generate a hydroxide precipitate (slurry containing zirconium hydroxide).

[0259] The obtained hydroxide precipitate was filtered and washed thoroughly with water, and the obtained hydroxide was dried at 105° C. for 24 hours. The dried hydroxide was heat treated (calcined) at 650° C. for 5 hours in air to obtain a porous zirconia-based composite oxide of Example 8.

[0260] (Example 9)

[0261] 145 g of zirconium oxynitrate dihydrate (converted to ZrO2: 67 g) was dissolved in ion exchange water, and the ZrO2 concentration was adjusted to 10 wt / v% to obtain a zirconium salt solution.

[0262] The obtained solution was placed in an autoclave, heated to 130°C and maintained for 1 hour, then 938 g of 5% sodium sulfate (sulfating agent) was added and maintained for 15 minutes. Then, the solution was cooled to room temperature (25°C) to obtain a slurry containing basic zirconium sulfate.

[0263] To the slurry containing basic zirconium sulfate were added 50 g of lanthanum nitrate solution (converted to La2O3: 5 g), 140 g of neodymium nitrate solution (converted to Nd2O3: 14 g), and 140 g of yttrium nitrate solution (converted to Y2O3: 14 g).

[0264] Next, 500 g of 25% sodium hydroxide (alkali for neutralization) was added over 60 minutes to generate a hydroxide precipitate (slurry containing zirconium hydroxide).

[0265] The obtained hydroxide precipitate was filtered and washed thoroughly with water, and the obtained hydroxide was dried at 105° C. for 24 hours. The dried hydroxide was heat treated (calcined) at 650° C. for 5 hours in air to obtain a porous zirconia-based composite oxide of Example 9.

[0266] (Example 10)

[0267] 152 g of zirconium oxynitrate dihydrate (70 g in terms of ZrO 2 ) was dissolved in ion exchange water, and the ZrO 2 concentration was adjusted to 10 wt / v % to obtain a zirconium salt solution.

[0268] The obtained solution was placed in an autoclave, heated to 120°C and maintained for 1 hour, then 980 g of 5% sodium sulfate (sulfating agent) was added and maintained for 15 minutes, and then cooled to room temperature (25°C) to obtain a slurry containing basic zirconium sulfate.

[0269] To the slurry containing basic zirconium sulfate was added 300 g of a neodymium nitrate solution (converted to Nd2O3: 30 g).

[0270] Next, 500 g of 25% sodium hydroxide (alkali for neutralization) was added over 60 minutes to generate a hydroxide precipitate (slurry containing zirconium hydroxide).

[0271] The obtained hydroxide precipitate was filtered and washed thoroughly with water, and the obtained hydroxide was dried at 105° C. for 24 hours. The dried hydroxide was heat treated (calcined) at 650° C. for 5 hours in air to obtain a porous zirconia-based composite oxide of Example 10.

[0272] (Example 11)

[0273] 134 g of zirconium oxynitrate dihydrate (converted to ZrO2: 64 g) was dissolved in ion exchange water, and the ZrO2 concentration was adjusted to 10 wt / v% to obtain a zirconium salt solution.

[0274] The obtained solution was placed in an autoclave, heated to 120°C and maintained for 1 hour, and then 882 g of 5% sodium sulfate (sulfating agent) was added and maintained for 15 minutes. The obtained solution was placed in an autoclave, heated to 120°C and maintained for 1 hour. Then, it was cooled to room temperature (25°C) to obtain a slurry containing basic zirconium sulfate.

[0275] To the slurry containing basic zirconium sulfate were added 120 g of lanthanum nitrate solution (converted into La2O3: 12 g), 250 g of yttrium nitrate solution (converted into Y2O3: 25 g), and 10 g of phosphoric acid solution (converted into P2O5: 1 g).

[0276] Next, 500 g of 25% sodium hydroxide (alkali for neutralization) was added over 60 minutes to generate a hydroxide precipitate (slurry containing zirconium hydroxide).

[0277] The obtained hydroxide precipitate was filtered and washed thoroughly with water, and the obtained hydroxide was dried at 105° C. for 24 hours. The dried hydroxide was heat treated (calcined) at 650° C. for 5 hours in air to obtain a porous zirconia-based composite oxide of Example 11.

[0278] (Example 12)

[0279] 119 g of zirconium oxynitrate dihydrate (converted to ZrO 2 : 50 g) was dissolved in ion exchange water, and the ZrO 2 concentration was adjusted to 10 wt / v % to obtain a zirconium salt solution.

[0280] The obtained solution was placed in an autoclave, heated to 120°C and maintained for 1 hour, then 826 g of 5% sodium sulfate (sulfating agent) was added and maintained for 15 minutes, and then cooled to room temperature (25°C) to obtain a slurry containing basic zirconium sulfate.

[0281] To the slurry containing basic zirconium sulfate were added 300 g of cerium nitrate solution (converted to CeO2: 30 g), 5 g of lanthanum nitrate solution (converted to La2O3: 5 g), and 50 g of neodymium nitrate solution (converted to Y2O3: 5 g).

[0282] Next, 500 g of 25% sodium hydroxide (alkali for neutralization) was added over 60 minutes to generate a hydroxide precipitate (slurry containing zirconium hydroxide).

[0283] The obtained hydroxide precipitate was filtered and washed with water, strontium hydroxide (converted to SrO: 1 g) was mixed into the obtained hydroxide, and dried at 105° C. for 24 hours. The dried hydroxide was heat-treated (calcined) at 700° C. for 5 hours in the air to obtain the porous zirconia-based composite oxide of Example 12.

[0284] (Comparative Example 1)

[0285] 117 g of zirconium oxynitrate dihydrate (54 g in terms of ZrO 2 ) was dissolved in ion exchange water, and the ZrO 2 concentration was adjusted to 10 wt / v % to obtain a zirconium salt solution.

[0286] 756 g of 5% sodium sulfate (sulfating agent) was added to the obtained zirconium salt solution and kept for 15 minutes. The obtained solution was placed in an autoclave, heated to 120°C, and kept for 1 hour and 30 minutes. Then, it was cooled to room temperature (25°C) to obtain a slurry containing basic zirconium sulfate.

[0287] To the obtained slurry containing basic zirconium sulfate, 300 g of cerium nitrate solution (converted to CeO2: 30 g), 80 g of neodymium nitrate solution (converted to Nd2O3: 8 g), and 80 g of praseodymium nitrate solution (converted to Pr6O3: 8 g) were added. 11 :8g).

[0288] Next, 500 g of 25% sodium hydroxide (alkali for neutralization) was added over 60 minutes to generate a hydroxide precipitate (slurry containing zirconium hydroxide).

[0289] The obtained hydroxide precipitate was filtered and washed thoroughly with water, and the obtained hydroxide was dried at 105° C. for 24 hours. The dried hydroxide was heat treated (calcined) at 700° C. for 5 hours in air to obtain a porous zirconia-based composite oxide of Comparative Example 1.

[0290] (Comparative Example 2)

[0291] 119 g of zirconium oxynitrate dihydrate (55 g in terms of ZrO 2 ) was dissolved in ion exchange water, and the ZrO 2 concentration was adjusted to 10 wt / v % to obtain a zirconium salt solution.

[0292] 770 g of 5% sodium sulfate (sulfating agent) was added to the obtained zirconium salt solution and kept for 15 minutes. The obtained solution was placed in an autoclave, heated to 110°C, and kept for 1 hour and 30 minutes. Then, it was cooled to room temperature (25°C) to obtain a slurry containing basic zirconium sulfate.

[0293] To the obtained slurry containing basic zirconium sulfate were added 400 g of a cerium nitrate solution (40 g in terms of CeO 2 ) and 50 g of a lanthanum nitrate solution (5 g in terms of La 2 O 3 ).

[0294] Next, 500 g of 25% sodium hydroxide (alkali for neutralization) was added over 60 minutes to generate a hydroxide precipitate (slurry containing zirconium hydroxide).

[0295] The obtained hydroxide precipitate was filtered and washed thoroughly with water, and the obtained hydroxide was dried at 105° C. for 24 hours. The dried hydroxide was heat treated (calcined) at 800° C. for 5 hours in air to obtain a porous zirconia-based composite oxide of Comparative Example 2.

[0296] (Comparative Example 3)

[0297] 182 g of zirconium oxychloride 8hydrate (converted to ZrO2: 70 g) was dissolved in ion exchange water, and then the acid concentration was adjusted to 0.67 N and the ZrO2 concentration to 4 wt / v% using 35% hydrochloric acid and ion exchange water to obtain a zirconium salt solution.

[0298] The obtained zirconium salt solution was placed in an autoclave and the pressure was set to 2×10 5 Pa, the temperature was raised to 120°C, 1035 g of 5% sodium sulfate (sulfating agent) was added at the same temperature, and the temperature was maintained for 15 minutes. Then, the mixture was cooled to room temperature (25°C) to obtain a slurry containing basic zirconium sulfate.

[0299] To the obtained slurry containing basic zirconium sulfate were added 200 g of cerium nitrate solution (converted to CeO2: 20 g), 20 g of lanthanum nitrate solution (converted to La2O3: 2 g) and 80 g of neodymium nitrate solution (converted to Nd2O3: 8 g).

[0300] Then, 500 g of 25% sodium hydroxide (alkali for neutralization) was added over 60 minutes. Zirconium hydroxide was generated by the neutralization.

[0301] Next, the zirconium hydroxide-containing slurry was filtered, washed with water, and then calcined at 600° C. for 5 hours to obtain an oxide.

[0302] (Comparative Example 4)

[0303] To 400 g of a solution of trivalent cerium nitrate (converted to CeO2 concentration: 10%), 8 g of a 35% hydrogen peroxide solution was added to obtain a cerium solution.

[0304] Next, 130 g of zirconium oxychloride octahydrate (converted to ZrO2: 50 g) was dissolved in ion exchange water, and the acid concentration was adjusted to 0.67 N and the ZrO2 concentration was adjusted to 4 wt / v% using 35% hydrochloric acid and ion exchange water. The prepared solution was heated to 2×10 5 Pa, 120°C, and when the temperature reached 120°C, 740 g of 5% sodium sulfate was added, and the mixture was kept at that temperature for 15 minutes, and then cooled to room temperature to obtain a basic zirconium sulfate slurry.

[0305] Then, the above cerium solution, 100 g of lanthanum nitrate (converted to La2O3 concentration: 10%) solution, and 500 g of 25% sodium hydroxide were added to the basic zirconium sulfate slurry, and decantation was repeated until impurities could be removed. Finally, the slurry was filtered and washed with water to obtain a hydroxide, which was calcined at 600°C for 5 hours to obtain an oxide.

[0306] [Determination of composition of porous zirconia-based composite oxide]

[0307] The compositions (calculated as oxides) of the porous zirconia-based composite oxides of Examples and Comparative Examples were analyzed using ICP-AES ("ULTMA-2" manufactured by HORIBA).

[0308] [Measurement of pore size distribution by BJH method (before heat treatment)]

[0309] The pore distribution of the porous zirconia-based composite oxides of the examples and comparative examples was obtained by the BJH method using a pore distribution measuring device "Belsorp mini II (manufactured by Microtrac BEL)". The measuring conditions are as follows:

[0310] <Measurement conditions>

[0311] Measuring device: Pore distribution measuring device (Belsorp mini II manufactured by MicrotracBEL),

[0312] Measuring range: 2~200nm,

[0313] Measurement points: 30 points,

[0314] Analytical method: BJH method.

[0315] For Examples 1 to 6 and Comparative Examples 1 to 4, the pore distribution of the porous zirconia composite oxide obtained is as follows: Figures 1 to 10 shown.

[0316] The obtained pore size distribution was used to determine the maximum value of the dV / dlogD peak in the range of 2 nm to 100 nm and the pore volume in the range of 2 nm to 100 nm.

[0317] [Measurement of pore distribution by mercury intrusion porosimetry (before heat treatment)]

[0318] The pore distribution of the porous zirconia-based composite oxides of the examples and comparative examples was obtained by mercury intrusion porosimetry using a pore distribution measuring apparatus ("Autopore IV9500" manufactured by Micromelitics). The measuring conditions were as follows:

[0319] <Measurement conditions>

[0320] Measuring device: Pore distribution measuring device (Autopore IV 9500 manufactured by Micromelitics),

[0321] Measuring range: 0.0036~10.3μm,

[0322] Measurement points: 120 points,

[0323] Mercury contact angle: 140 degrees,

[0324] Mercury surface tension: 480 dyne / cm.

[0325] The obtained pore distribution was used to determine the pore volume in the entire measurement range (0.0036 μm to 10.3 μm) and the pore volume in the range of more than 100 nm and less than or equal to 1000 nm.

[0326] [Measurement of pore size distribution by BJH method (after heat treatment)]

[0327] The porous zirconia-based composite oxides of the examples and comparative examples were heat treated at 1000°C for 3 hours under atmospheric pressure (0.1013 MPa) and air atmosphere. Then, the pore distribution was obtained by the BJH method using a pore distribution measuring device "Belsorp mini II (manufactured by Microtrac BEL)". The measurement conditions were the same as those for the measurement of pore distribution by the BJH method before the heat treatment.

[0328] For Examples 1 to 6 and Comparative Examples 1 to 4, the pore distribution of the porous zirconia composite oxide obtained is as follows: Figures 11 to 20 shown.

[0329] The obtained pore size distribution was used to determine the maximum value of the dV / dlogD peak in the range of 2 nm to 100 nm and the pore volume in the range of 2 nm to 100 nm.

[0330] [Measurement of pore distribution by mercury intrusion porosimetry (after heat treatment)]

[0331] The porous zirconia composite oxides of the examples and comparative examples were heat treated at 1000°C for 3 hours under atmospheric pressure (0.1013 MPa) and air atmosphere. Then, the pore distribution was obtained by mercury intrusion using a pore distribution measuring device ("Autopore IV 9500" manufactured by Micromelitics). The measuring conditions were the same as those for the measurement of pore distribution by mercury intrusion before heat treatment.

[0332] The obtained pore distribution was used to determine the pore volume of the entire measurement range and the pore volume of the range exceeding 100 nm and 1000 nm or less.

[0333] [Measurement of specific surface area before heat treatment]

[0334] The specific surface areas of the porous zirconia-based composite oxides of Examples and Comparative Examples were measured by the BET method using a specific surface area meter ("Macsorb", manufactured by MOUNTECH Co., Ltd.).

[0335] [Measurement of specific surface area after heat treatment at 1000°C for 3 hours]

[0336] The porous zirconia composite oxides of the examples and comparative examples were heat treated at 1000°C for 3 hours under atmospheric pressure (0.1013 MPa) and air atmosphere. The specific surface area of ​​the porous zirconia composite oxide after heat treatment at 1000°C for 3 hours was measured in the same manner as in "Measurement of specific surface area before heat treatment". The results are shown in Tables 1 and 2.

[0337] [Measurement of specific surface area after heat treatment at 1100°C for 3 hours]

[0338] The porous zirconia composite oxides of the examples and comparative examples were heat treated at 1100°C for 3 hours under atmospheric pressure (0.1013 MPa) and air atmosphere. The specific surface area of ​​the porous zirconia composite oxide after heat treatment at 1100°C for 3 hours was measured in the same manner as in "Measurement of specific surface area before heat treatment". The results are shown in Tables 1 and 2.

[0339] [Particle size D 10 , particle size D50 , particle size D 90 Determination of

[0340] 0.15 g of the porous zirconia composite oxide (powder) of the embodiment and the comparative example and 40 ml of a 0.2% sodium hexametaphosphate aqueous solution were placed in a 50 ml beaker, dispersed for 5 minutes at a frequency of 28 kHz using an ultrasonic cleaner "VS-100III" (VELVO-CLEAR Co., Ltd.), and then placed in an apparatus (a laser diffraction particle size distribution measuring apparatus ("SALD-2300" manufactured by Shimadzu Corporation, Japan)) for measurement. The results are shown in Tables 1 and 2.

[0341] Table 1

[0342]

[0343] Table 2

[0344]

Claims

1. A porous zirconia-based composite oxide, characterized in that: In the range of 2 nm to 200 nm in the pore size distribution based on the BJH method, the following (1) to (3) are satisfied: The volume of pores in the range of more than 100 nm and less than or equal to 1000 nm in the pore distribution based on mercury intrusion porosimetry is 0.01 cm 3 / g above 0.25cm 3 / g or less, (1) The dV / dlogD peak is within the range of 2nm to 100nm. (2) the maximum value of the dV / dlogD peak is 1.5 or more and 5.0 or less, (3) The pore volume in the range of 2 nm to 100 nm is 0.30 cm 3 / g above 1.50cm 3 / g or less.

2. The porous zirconia-based composite oxide according to claim 1, characterized in that: The following (4) to (6) are satisfied in the range of 2 nm to 200 nm in the pore distribution according to the BJH method after heat treatment at 1000°C for 3 hours under atmospheric pressure and air atmosphere, The volume of pores in the range of more than 100 nm and less than or equal to 1000 nm in the pore distribution determined by mercury intrusion porosimetry after heat treatment at 1000°C for 3 hours under atmospheric pressure and air atmosphere was 0.01 cm 3 / g above 0.20cm 3 / g or less, (4) The dV / dlogD peak is within the range of 2nm to 100nm. (5) the maximum value of the dV / dlogD peak is 1.0 or more and 4.0 or less, (6) The pore volume in the range of 2 nm to 100 nm is 0.25 cm 3 / g above 1.00cm 3 / g or less.

3. The porous zirconia-based composite oxide according to claim 1 or 2, characterized in that: The specific surface area after heat treatment at 1000°C for 3 hours under atmospheric pressure and air atmosphere is 45m 2 / g above 100m 2 / g or less.

4. The porous zirconia-based composite oxide according to claim 1 or 2, characterized in that: The specific surface area is 45m 2 / g above 150m 2 / g or less.

5. A method for producing a porous zirconia-based composite oxide according to claim 1 or 2, characterized in that: include: In the first step, a zirconium salt solution is heated at a temperature of 100° C. to 150° C. to generate a portion of hydrated zirconium oxide. as well as The second step is to add a sulfating agent after the first step to obtain a slurry containing basic zirconium sulfate.

Citation Information

Patent Citations

  • Zirconia-based porous body and its production method

    JP2006036576A

  • Porous zirconia-based powder and its manufacture method

    JP2008081392A

  • Cerium-zirconium-based composite oxide and its manufacturing process

    JP2009249275A

  • Zirconia-based porous body and method for producing the same

    JP2015189655A

  • Cerium and zirconium based mixed oxides

    JP2019521937A